How did media present the radiation risks after the Fukushima accident: a content analysis of newspapers in Europe. (6th June 2016) - Tomkiv, Yevgeniya; Perko, Tanja; Oughton, Deborah H; Prezelj, Iztok; Cantone, Marie C; Gallego, Eduardo
Abstract: Any activity that might result in exposure of a population to contaminants requires communication of the associated risks. This communication is complicated by several factors including public perceptions, distrust, uncertainties in risk assessment and news media. These factors are especially prominent in communication of risks from ionizing radiation. A number of guidelines about the communication of risks related to radiation exposures have been made by national and international authorities and other stakeholders. The present paper investigates whether those guidelines were followed and evaluates how the radiation risk related information was presented in European newspapers and Russia in the aftermath of the Fukushima accident. It examines the use of measurement units and risk comparisons, the quality of the statements on radiation risk related issues and the use of visual materials in 1340 newspaper articles from Belgium, Italy, Norway, Russia, Slovenia and Spain. Our results indicated several misinterpretations and misrepresentations of radiological risks in the newspaper articles. We also show an inconsistency in the information that was reported with advice provided to risk communicators (e.g. authorities and experts) in the guidelines. The results suggest that risk communicators should improve their communication practices regarding radiological risks, in order to improve emergency management response.